Dissolution of coated microbubbles: The effect of nanoparticles and surfactant concentration - Azmin, M; Mohamedi, G; Edirisinghe, M; Stride, E (2012)
The ability of solid particles to stabilise emulsions is a well known phenomenon which has recently been demonstrated for the stabilisation of gas bubbles. In this paper, a new theoretical model is developed which describes how an adsorbed layer of solid nanoparticles modifies the interfacial tension and diffusivity of a gas bubble in a liquid and hence its stability. In agreement with experimental observations on microbubbles coated with 15 nm diameter spherical gold particles, the results of simulations with the model indicate that the particles substantially decrease the rate at which bubble dissolution occurs and enables them to maintain a stable radius once a critical particle concentration has been reached. © 2012 Elsevier B.V.